Nilai Moral dalam Cerita Pendek Hasil Belajar Peserta Didik SMK N 6 Semarang - Rudi Dwi Purwanto (Institut Agama Islam Negeri Curup, 2023)
This study aims to find the moral values contained in historical themed short stories produced by students of SMK N 6 Semarang. The research method used in this study is a qualitative descriptive method. The theory of moral values used in this study consists of four divisions of types of moral values, namely, 1. moral values of divinity, 2. moral values of ideology and philosophy, 3. moral values of ethics and decency, and 4. moral values of discipline and law. The time for collecting research data was in the odd semester in the learning material for writing short stories with the theme of Indonesian history in class XI fashion 2, SMK N 6 Semarang. The results of this study found various moral values contained in historical-themed short stories by students of SMK N 6 Semarang. The results of the analysis of short stories made by students of SMK N 6 Semarang, there are eleven moral values contained in them. The results of this study show that the most moral values are ethical moral values, moral moral values with 5 (five) findings of moral values, then there are ideological and philosophical values, there are 4 (four) moral values, and finally there is 1 moral value, namely moral values of divinity, discipline and law. The first short story contains the moral values of ideology and philosophy, the second short story contains the moral values of ethics and decency, the third short story contains the moral values of ideology and philosophy, the fourth short story contains the moral values of ethics and decency, the fifth short story contains the moral values of ethics and decency, the sixth short story contains moral values divine and ideological morals, the seventh short story contains moral values of ethics and decency, and the eighth short story contains moral values of discipline and law.